Boom! : [compact disc, abridged] : voices of the sixties : personal reflections on the '60s and today - Brokaw, Tom (Random House Audio, 2007)
Redefines the tumultuous 1960s, a decade that saw the rise of the rebellious children of the greatest generation, to reveal how American social, political, economic, and cultural institutions were transformed by an era of dramatic change.